Millennial-Scale Denitrification Dynamics in the Arabian Sea: A Paleo-Bibliometric Review - Dhiraj Shinde,; Yoganandan Veeran,; Shubham Tripathi,; Shahin Shajahan,; Ritesh Kumar, (The Bioscan, 2025)
Arabian Sea (AS) is a region of significant oceanographic and climatic importance, characterized by a monsoon-driven productivity and extensive oxygen minimum zones (OMZs). This review synthesizes millennial-scale studies on denitrification in the AS, examining its links with past climate changes, oceanic oxygen levels, and biogeochemical cycles. Denitrification, a key microbial process transforming bioavailable nitrogen to inert nitrogen gas, plays a crucial role in the nitrogen budget of marine ecosystems, particularly in OMZs where low oxygen conditions favor such pathways. Reconstructions of past denitrification, based on isotopic and geochemical proxies preserved in sediments, reveal strong links with fluctuations in the South Asian Monsoon (SAM) and associated nutrient supply. This review highlights the sensitivity of OMZs to climatic and anthropogenic forcing, providing insights into how future climate change may alter nitrogen cycling and OMZ dynamics. The findings contribute to improving predictive models of biogeochemical feedbacks in the global climate system.